PURBA 2016: The 5th workshop on pervasive urban applications - Santi Phithakkitnukoon (2018)
© 2016 ACM. The 5th Workshop on Pervasive Urban Applications (PURBA 2016) aims to build on the success of the previous workshops organized in conjunction with the Pervasive 2011, Pervasive 2012, UbiComp 2013, and UbiComp 2015, to continue to disseminate the results of the latest research outcomes and developments of ubiquitous computing technologies in urban areas. All workshop contributions will be published in supplemental proceedings of the UbiComp 2016 conference and included in the ACM Digital Library.